(3dhGbM GdCfhGQ GdbOSjI GdefNH ef GdaJhMGJ GdecjIs - (3YHO GdhgGH Hf CMeO Hf Ydj GdnMnfaj, fSHg Edi eMeO GHf GdMfajI, GdTYQGfj, CHh eMeO , J (B973 (3g`s
(3ChdgG (B:s
(3GdMeO ddg hMOg ef GdYghO GdeMeOjI ddEeGe GdYGQa HGddg JYGdi SjOi YHO GdhgGH GdTYQGfi eGfUI CNP YdjfG GdYgO GdYGe ef QShd Gddg Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3abGd CQe HgG hCfJ JUYO aQejJgG hUYOJ hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B180s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdeLGejYs